2006
DOI: 10.1152/jn.00386.2005
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-Gated Chloride Channels Depress Synaptic Transmission in Rat Hippocampus

Abstract: An inhibitory role for strychnine-sensitive glycine-gated chloride channels (GlyRs) in mature hippocampus is beginning to be appreciated. We have reported previously that CA1 pyramidal cells and GABAergic interneurons recorded in 3- to 4-wk-old rat hippocampal slices express functional GlyRs, dispelling previous misconceptions that GlyR expression ceases in early development. However, the effect of GlyR activation on cell excitability and synaptic circuits in hippocampus has not been fully explored. Using whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 72 publications
4
56
0
Order By: Relevance
“…Reduction of GlyRs suppression function facilitates LTD induced by repetitive paring of postsynaptic spike and presynaptic stimulations, whereas activation of GlyRs with high-level glycine (1.0 mM) counteracts this form of LTD. In this study, it is possible that activation of GlyRs by 1.0 mM glycine (in 4.0 mM Mg 2 + -containing perfusing medium) suppresses excitatory neurotransmission, as demonstrated by a recent study (Song et al, 2006). This effect might occur more rapidly than LTD induction and thus excludes further LTD elicited by 10 Hz induction protocol.…”
Section: Involvement Of Glyrs In Ltd Inductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Reduction of GlyRs suppression function facilitates LTD induced by repetitive paring of postsynaptic spike and presynaptic stimulations, whereas activation of GlyRs with high-level glycine (1.0 mM) counteracts this form of LTD. In this study, it is possible that activation of GlyRs by 1.0 mM glycine (in 4.0 mM Mg 2 + -containing perfusing medium) suppresses excitatory neurotransmission, as demonstrated by a recent study (Song et al, 2006). This effect might occur more rapidly than LTD induction and thus excludes further LTD elicited by 10 Hz induction protocol.…”
Section: Involvement Of Glyrs In Ltd Inductionmentioning
confidence: 60%
“…However, these results were obtained in the presence of the GlyR antagonist, strychnine, in all of the solutions to deliberately exclude the potential activation of GlyRs (Lu et al, 2001). A recent study reported the acute suppressive action of both EPSCs in CA1 pyramidal neurons and IPSCs in interneurons by glycine (Song et al, 2006). This inhibitory effect only lasted for around 15 min, and the EPSCs recovered after the washout of glycine.…”
Section: Involvement Of Glyrs In Ltd Inductionmentioning
confidence: 95%
See 1 more Smart Citation
“…GlyRs containing a1 and a3 subunits are expressed in spinal cord and brainstem circuits implicated in startle disease, inflammatory pain and rhythmic breathing. 51 Although GlyRs are expressed in the hippocampus and cortex, [21][22][23][24][25][26][27] their role in development has been largely overlooked. Over the past few years, we and others have discovered that GlyRs are highly expressed by specific neurons and progenitors of the cerebral cortex where they control critical developmental features.…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic GlyRs control synaptic transmission of sensory stimuli and are involved in the generation of motor outputs in the spinal cord. 20 These receptors are also expressed in the hippocampus [21][22][23][24][25] and in the cortex. 26,27 Importantly, GlyR heteromers cluster at the presynaptic membrane to control neurotransmitter release in the medial nucleus of trapezoid body in the brainstem, 28 the spinal cord 29,30 and the ventral tegmental area.…”
mentioning
confidence: 99%